Formulation and Evaluation of Luliconazole nanosponge gel using Experimental design - Narender Malothu; Sadhana Noothi; Anka Rao Areti; Vishnu Pulavarthy (Indonesian Journal of Pharmacy, 2024)
Different approaches are being in the practice for the topical application of antifungal drugs, although in a few cases, they have been found less efficient because of their poor cutaneous availability and permeability. Luliconazole (LUL) is one of the antifungal medications that is being used for the treatment of various superficial infections. The poor permeability of LUL is regarded to be a factor for its reduced efficacy. Hence, the current study aimed to develop a nanosponge hydrogel that would improve dermal availability and permeability. A set of nanosponge formulations (L1-L18) were designed with the help of central composite design (Design Expert 13, state ease Inc., Minneapolis, MN, USA). L1-L18 was prepared by using the emulsion solvent evaporation technique. The nanosponges were characterized for drug-excipient compatibility (FTIR, P-XRD, and DSC), and particle size, polydispersibility index, zeta potential, entrapment efficiency (EE), and in vitro drug release; further optimized. The optimized nanosponge formulation (L18) was taken to produce six hydrogels (LF1-LF6) of LUL by varied proportions of the gelling agent. In this process, initially, the gel was constituted with Carbopol 934/ sodium CMC/HPMC. Later, attained hydrogel texture was evaluated for its viscosity, swelling, and membrane permeability, followed by in vitro drug release, and antifungal efficacy study. The nanosponge formulations (L1-L17) had an average particle size of 109±0.45 to 386±0.34 nm, entrapment efficiency of 35.45±0.46- 89.65±0.37 % with 84.67±0.54 -99.65±0.48 % of drug release for 8 h. The formulation L18 was predicted with better responses in particle size,  EE, and drug release i.e., 378±0.25 nm,  84.65±0.45%, and of 96.18±0.54%, respectively for 8 h. Out of six formulated nanosponge gels (LF1-LF6),  LF2 showed an optimal viscosity (25.69 ±0.45 pa.S), pH (6.87±0.56) and % drug release (80.65 ±0.64%) in 8 h. Drug release was governed by non-fickian diffusion mechanisms and zero-order. Developed nanosponge hydrogel was found as stable and had a high rate of permeation with better retention which can be effective enough in topical applications.